Respon Pertumbuhan Dan Produksi Mentimun Baby (Cucumis Sativus L.) Pada Berbagai Aplikasi Eco-Enzym Dan Plant Growth Promoting Rhizobacteria - Okti; Saptaningsih Sumarmi; Meilany Nonsi Tentua; Hani Andrasasi (Jurnal Penelitian Pertanian Terapan, 2023)
Consumption of baby cucumbers in fresh form by the community is one of the factors driving the cultivation of environmentally friendly cucumbers so that they are safe for health and the environment. The use of PGPR (plant growth promoting rhizobacteria) and eco-enzymes to sufficient the nutrient needs of cucumber plants. This study aims to examine the use of PGPR and eco-enzymes in environmentally friendly baby cucumber cultivation. The study was arranged in an RCBD (Randomized Complete Block Design) design in 3 blocks with 6 treatments, namely control (without fertilizer), eco-enzyme concentration of 5 ml/l water, bamboo root PGPR 10 ml/l water, banana weevil PGPR 10 ml/l water, Eco-enzyme 2.5 ml/l water + PGPR bamboo root 5 ml/l water, eco-enzyme 2.5 ml/l water + PGPR banana hump 5 ml/l water. The research was conducted in Sawahan Hamlet, Pandowoharjo Village, Sleman DIY, alluvial soil type. The research data were analyzed using the Analysis of Variance at the 5% real level. To find out the real difference between treatments, Duncan's multiple distance test was carried out at the 5% real level. The results showed that the use of eco-enzymes could increase root dry weight, fruit number and fruit weight of baby cucumbers. The use of PGPR can increase the number of baby cucumbers. PGPR can increase cucumber fruit weight when applied with eco-enzymes.